Production and printing of solvent-based fluorescent ink for using in anti-counterfeiting documents - ÖZCAN, ARİF (My University, 2022)
© 2022 Authors.Security inks are used in areas such as money, expensive products, identity cards, passports. Generally, they are more expensive than conventional inks. A good security ink is expected to be fairly inexpensive and non-replicable. Pigments used in security ink are usually produced from rare earth elements. It is very difficult to produce ink from rare earth elements and high performance ink carrier systems are needed. There is no need for special carrier systems to produce ink from organic fluorescent pigments, and they allow cheaper ink production while reducing reproducibility. In this study, it is aimed to produce ink using organic-based fluorescent pigment. For this purpose, solvent-based ink formulations containing commercial solvent based organic fluorescent blue pigment in different ratios were prepared with polyurethane resin. The prepared inks were printed on the paper surface with the inkjet printing system. The colour properties of the prints obtained were determined under daylight and UV light. In addition, the gloss, adhesion, abrasion resistance, light fastness and drying times of the prints were determined. As a result, it has been determined that the ink produced is transparent in daylight, has a blue glow in UV light and can be used as a security ink in valuable documents.
Keywords: Bilgisayar Bilimleri; Bilgisayar Grafiği; Mühendislik ve Teknoloji; Computer Sciences; Computer Graphics; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Bilgisayar Bilimi; BİLGİSAYAR BİLİMİ, İNTERDİSİPLİNER UYGULAMALAR; Engineering, Computing & Technology (ENG); COMPUTER SCIENCE; COMPUTER SCIENCE, INTERDISCIPLINARY APPLICATIONS; Bilgisayar Grafikleri ve Bilgisayar Destekli Tasarım; Fizik Bilimleri; Bilgisayar Bilimi Uygulamaları; Computer Graphics and Computer-Aided Design; Physical Sciences; Computer Science Applications; anti-counterfeiting; fluorescent; printability; security ink